Effect of Gamification on the Motivation of Computer Programming Students - D Cuervo-Cely, Karen; Restrepo-Calle, Felipe; J Ramírez-Echeverry, Jhon (Journal of information technology education, 2022)
Aim/Purpose: The purpose of this research is to examine the effect of computer-assisted gamification on the learning motivation of computer programming students. Background: The teaching-learning of computer programming involves challenges that imply using learning environments in which the student is actively involved. Gamification is an innovative approach that allows the creation of environments using game-related elements in order to increase the levels of participation, engagement, and motivation of the participants. Several studies have integrated gamification in academic contexts, where generally the qualitative results show remarkable effects in different aspects analyzed; however, there is still no consensus on the quantitative results presented in different investigations. For this reason, it is necessary to conduct more empirical studies in computer programming learning environments to better understand the impact of gamification on aspects such as students’ motivation to learn. Methodology: A quasi-experimental mixed explanatory study was designed and carried out in which a gamified tool was integrated into the methodology of an Intro-duction to computer programming course. Through a literature review and a comparative analysis, we selected CodeGym as the computer-assisted gamified environment suitable for integration into the activities of the course. Subsequently, we proposed an educational intervention where the instruments were applied to characterize the motivational construct by means of the self-report questionnaire MSLQ-Colombia and a survey of student opinion. The MSLQ-Colombia questionnaire characterizes distinctive features of students’ motivation to learn. This instrument was adapted and validated to Spanish based on the original MSLQ (Motivated Strategies for Learning Questionnaire). Forty-eight students participated in this study, distributed in two control groups and one experimental group selected by means of a non-probabilistic convenience sampling technique. Contribution: The effects reported through this research provide empirical evidence related to the effect of computer-assisted gamification on students’ motivation to learn. The results contribute to understanding the effects that gamification can generate in the motivation of computer programming students. Findings: The quantitative results obtained through the MSLQ-Colombia showed that the students in the experimental group significantly increased the levels related to the motivational aspects of Task Valuation. The results obtained by the survey (quantitative and qualitative data) confirmed the quantitative effect found and, additionally, generated inputs related to other motivational aspects: the participants expressed that due to the development of the practical exercises proposed with CodeGym, they felt authentic desires to learn (Orientation of the study activities towards Intrinsic Goals), greater self-confidence to approach the learning tasks (Beliefs of Control of Learning), and better expectations to achieve their learning goals in the subject (Expectations of Self-Efficacy in Learning). Recommendations for Practitioners: The computer-assisted gamification generated a good reception by the students of Computer Programming, making the teaching-learning process pleasant and favoring the interest towards the topics generally considered as challenging. It is recommended that teachers in the area of computer programming continue adopting and using gamified tools that support and facilitate the appropriation of knowledge of their students in a dynamic and innovative way. Recommendation for Researchers: The empirical results reported in this study allow a better understanding of the real effects that gamification can have on programming students’ motivation to learn. However, there are still great challenges in trying to understand and generalize these findings. It would be interesting to deepen the results obtained by integrating gamification in environments where there are more participants and longitudinal studies where the impact is analyzed over time. Impact on Society: The results of this research showed that computer-assisted gamification generated a significant increase in the ratings related to the interest, importance, or liking towards the topics proposed in the subject of computer programming. Additionally, the participants felt authentic desires to learn (Orientation of the study activities towards Intrinsic Goals), greater self-confidence to approach the learning tasks (Beliefs of Control of Learning), and better expectations to achieve their learning goals in the subject (Expectations of Self-Efficacy in Learning). All mentioned contribute to the understanding of the real effects related to gamification in computer programming because in this way teachers and students can appropriate these methodologies in an informed way. Future Research: It would be interesting to be able to replicate the intervention carried out in this study in longitudinal research that would allow us to know the effects of gamification over a long period of time. It is also necessary to understand, through more experimental or quasi-experimental studies, the effects of computer-assisted gamification on other aspects such as academic performance, learning, active participation of students, among others.